Thermodynamic Study of Complexation of Iminobis(N-2-aminoethylacetamide)Polysiloxane Immobilized Ligand System with Co2+, Ni2+ and Cu2+ Ions - M. EL-ASHGAR, NIZAM; J. YASSEEN, ZEYAD (Asian Journal of Chemistry, 2010)
The thermodynamic parameters characterizing the complexation of Co(II), Ni(II) and Cu(II) metal ions with porous solid iminobis(N-2-aminoethylacetamide) polysiloxane-immobilized ligand system of the general formula P-(CH2)3-N(CH2CONHCH2CH2NH2)2. where P represents [Si-O]n siloxane network, were investigated. The complexations were achieved at pH 5. The negative values of ΔG and the positive values of ΔH indicate that the complex formation proceeds spontaneously and endothermically. The positive changes of both enthalpy and entropy during the complexation clearly indicate that the driving force for complexation is enthalpically unfavoured but entropically favoured resulting from the dehydration during the complex formation. The plots of log KD vs. the reciprocal of absolute temperature were linear for all studied cases and were utilized to calculate the enthalpies of complexation reactions.